Impact of e-procurement adoption on company performance: Evidence from Indonesian manufacturing industry - Ilyas Masudin; Ganis Dwi Aprilia; Adhi Nugraha; Dian Palupi Restuputri (Logistics, 2021)
This study was conducted to determine the performance impact of e-procurement adoption in Indonesian manufacturing companies. This study consists of four variables: top management support, information quality, implementation of e-procurement, and company performance. Pilot testing questionnaires were used to test whether the respondents understood the questions given by the researcher. After conducting the pilot test, the final questionnaire was distributed to respondents. The pilot test results and the final questionnaire were analyzed using Statistical Package for Social Science (SPSS) version 21 and SmartPLS v3.0 software to determine the relationship between variables. The results of this study support the acceptance of three hypotheses. The results indicate that top management support has a significant effect on e-procurement implementation. Other results show that information quality has a significant effect on e-procurement implementation, while e-procurement implementation has a significant effect on company performance. From the findings of this article, recommendations from a management perspective are discussed to increase management awareness in adopting electronic procurement.
Keywords: 650; e-procurement; information quality; management support; performance